Torsional Behavior of Steel-Concrete-Steel Sandwich Beams with Welded Stirrups as Shear Connectors - Samoel M. Saleh; Fareed H. Majeed; Osamah Al-Salih; Haleem K. Hussain (Salehan Institute of Higher Education, 2023)
The structural performance of a steel-concrete-steel sandwich beam (SCSSB) with welded stirrups to the steel skin plates as shear connections exposed to a pure torsion load was studied in this paper. Eight SCSSB specimens were fabricated and tested under pure torsion. The effects of the compressive strength of the concrete core, 26 and 35 MPa, the thickness of the top and bottom steel skin plates, 2 and 4 mm, and the degree of shear interaction, which represents the number of beam stirrups, between the steel skin plates and the concrete core are 75, 100, and 125%. The experiment beams revealed a similar mode of failure for all SCSSB specimens regarding all considered variables, which started with inclined cracks along the specimens’ side faces and ended with local separation between one of the steel skin plates (top or bottom) and the concrete core. In addition, the experiment results showed an increase in the torsional strength with the increase in the shear connection ratio and the thickness of the steel skin plate, as well as with the increase in the strength of the concrete core. However, it was observed that the torsional ductility of the tested beams is proportional directly to the steel skin plate thickness and degree of interaction and inversely with the concrete compressive strength. The results showed that the use of steel skin plates with welded stirrups as a shear connection could reduce the negative effect of increasing the compressive strength of the concrete core on the torsional ductility of SCSSB. Doi: 10.28991/CEJ-2023-09-01-016 Full Text: PDF